Gender differences in patients admitted to a certified German Chest Pain Unit: results from the German Chest Pain Unit Registry - Settelmeier, Stephan; Rassaf, Tienush; Hochadel, Matthias; Voigtländer, Thomas; Münzel, Thomas; Senges, Jochen; Breuckmann, Frank; Giannitsis, Evangelos (Cardiology, 2020)
Introduction: Gender-specific atypical clinical presentation in acute coronary syndrome and sex-specific outcomes in cardiovascular disease in women are well known. The aim of this study is to analyze possible differences between men and women presenting to certified German chest pain units (CPUs). Methods: Data from 13,900 patients derived from the German CPU registry were analyzed for gender differences in patient characteristics, cardiovascular disease manifestation, critical time intervals, treatment and prognosis. Results: A total of 37.8% of patients were female. Typical chest pain occurred more frequently in men, while atypical symptoms occurred more frequently in women. Female gender was associated with longer pre- and in-hospital time delays. Women were more often diagnosed with a nonischemic origin of pain. In a 3-month follow-up, there was no gender-specific difference in combined major adverse coronary and cerebrovascular events. Discussion/Conclusion: This study points out gender-specific differences in prehospital time intervals and a significantly higher percentage of atypical symptoms in suspected myocardial ischemia as well as more noncoronary diagnoses in women. Symptom awareness and a broader diagnostic workup in women are essential.
Gesehen am 13.11.2020